2019
DOI: 10.1158/0008-5472.can-19-1698
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome: A New Player in Breast Cancer Metastasis

Abstract: There is increasing interest in the role of the gut microbiome in health and disease, and a number of observational and in vitro studies have suggested it may play a role in breast cancer development and progression. Buchta Rosean and colleagues present the first functional evidence that a preexisting disturbance in the gut microbiome leads to increased breast cancer cell metastasis in a mouse model. This discovery places the gut microbiome as a new player in breast cancer metastasis; however, further studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 12 publications
2
30
0
Order By: Relevance
“…In the previous study [19], we showed that LCA supplementation in vivo inhibits tumor growth, metastasis formation, epithelial-to-mesenchymal transition, and bioenergetic changes [19]. These findings are supported by patient observation and wet chemistry experiments that have been carried out by others [59,60,61].…”
Section: Resultssupporting
confidence: 69%
“…In the previous study [19], we showed that LCA supplementation in vivo inhibits tumor growth, metastasis formation, epithelial-to-mesenchymal transition, and bioenergetic changes [19]. These findings are supported by patient observation and wet chemistry experiments that have been carried out by others [59,60,61].…”
Section: Resultssupporting
confidence: 69%
“…We assessed whether IS can modulate cancer hallmarks that were modulated by other cytostatic bacterial metabolites [ 16 , 17 , 41 , 47 , 61 , 62 , 63 , 64 , 65 ]. First, we assessed oxidative/nitrosative stress markers, as these are major regulators of cancer hallmarks and cancer progression [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The underlying molecular mechanism involved in IS effects on tumor progression is the reversal of the epithelial-to-mesenchymal transition, similar to other metabolites [ 16 , 17 , 40 , 41 , 44 , 45 , 47 ]. Reverting or inhibiting EMT slows cell movement, diapedesis, and metastasis formation, as was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial metabolites modulate the redox balance of cancer cells [24,34], as well as cancer cell metabolism [22,23]. These processes culminate in cytostasis, a reprogramming of the epithelial-mesenchymal transition leading to decreased cancer stem cells [22][23][24][25]29,34,35,45]. These basic events are the pillars for the inhibition of cancer cell growth, movement, and metastasis formation [46][47][48].…”
Section: Pancreatic Adenocarcinoma An Unmet Medical Needmentioning
confidence: 99%